Socio-Demographic Profile of Infant Mortality by Verbal Autopsy in Urban Area of Bhavnagar, Gujarat - Rathod, Sanat; Singh, MP; Damor, Rahul; Jankar, Dharmendra; Gosalia, Vibha; Patel, Harshad; Raval, Devang (National Journal of Community Medicine, 2011)
Objectives: To study socio-demographic profile of all registered infant deaths in Bhavnagar city. Materials and Method: This was a community-based retrospective analytical study carried out in municipal corporation area of Bhavnagar city for which list of all registered infant deaths from 1st January 2009 to 31st December 2009 from municipal corporation, Bhavnagar was obtained. Data collection was carried out between January to May 2010 at respondent’s house with help of restructured verbal autopsy questionnaire developed by WHO. Result: Out of 96 total verbal autopsies 73(76%) infant deaths were in neonatal period chiefly focus in early neonatal period (62.5%). Male infant was 57.3% & 42.7% were female. Average family size was 4.9%. 61.5% from socio-economic class IV and 38.5% from class V. Poor housing was reported in 90% cases. Mother age less than 20 years at time of birth of the baby was in 15%. >1/3rd infant deaths in gravida & parity one. In 53.9% cases birth spacing was <2years. Conclusion: By studying verbal autopsy, this study shows how important it is to correctly identify socio-demographic factors responsible for infant deaths. The present study concluded highest chances of infant deaths in ENP (Early Neonatal Period) mainly within one hour with significant male infant deaths in ENP. Most deaths were in lower socio-economic strata & first gravida/parity with birth spacing less than two years.